2008
DOI: 10.1111/j.1440-1746.2008.05572.x
|View full text |Cite
|
Sign up to set email alerts
|

Changing trends in the proportion of adenocarcinoma of the esophagogastric junction in a large tertiary referral center in Japan

Abstract: An increasing trend of adenocarcinoma of EGJ is observed in this study of patients operated on for gastric adenocarcinoma from 1962 to 2005 in a large tertiary referral center in Japan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
189
1
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(196 citation statements)
references
References 26 publications
5
189
1
1
Order By: Relevance
“…Recent studies indicate that the incidence rate of gastric cardia cancer is as high as esophageal cancer in the high-incidence area of esophageal cancer. Epidemiological studies also have reported an increasing incidence of gastric cardia cancer in some Asian countries during the past few decades (Blaser et al, 2002;Tony et al, 2007;Kusano et al, 2008;Zhou et al, 2008;Deans et al, 2011), owning to the development of the early diagnosis of gastric cardia cancer and its clear definition. Screening program of esophageal and gastric cardia cancer screening of Linzhou in [2005][2006] has proofed it and has also showed the rise of the ratio of esophageal to gastric cardia cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that the incidence rate of gastric cardia cancer is as high as esophageal cancer in the high-incidence area of esophageal cancer. Epidemiological studies also have reported an increasing incidence of gastric cardia cancer in some Asian countries during the past few decades (Blaser et al, 2002;Tony et al, 2007;Kusano et al, 2008;Zhou et al, 2008;Deans et al, 2011), owning to the development of the early diagnosis of gastric cardia cancer and its clear definition. Screening program of esophageal and gastric cardia cancer screening of Linzhou in [2005][2006] has proofed it and has also showed the rise of the ratio of esophageal to gastric cardia cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Data from prior Asian studies have been inconsistent with regard to the incidence of GCA. Some showed an increase in incidence in Japanese, Chinese, Korean, Singaporean and South Indian populations while others showed no change [19][20][21][22][23][24]. A metaanalysis by Corley et al showed that there was no clear association between GCA and obesity in the Asian population and one study had even showed negative correlation [15,25].…”
Section: What Does the Current Study Add?mentioning
confidence: 99%
“…Tranqüiliza o paciente 19 e identifi ca tanto os casos de dispepsia funcional (a maioria dos da obesidade. Há uma maior preocupação hoje em dia com as complicações da DRGE, já que parece estar havendo um aumento da incidência do adenocarcinoma da junção gastro-esofágica nos países ocidentais 18 e mesmo no Japão 10 . casos), que são benignos e não vão exigir muitos recursos no seu acompanhamento, bem como os casos de neoplasia gástrica.…”
Section: Endoscopia Inicialunclassified